Analisis Penerapan Pasal tentang Tidak Melaporkan Adanya Tindak Pidana Narkotika Golongan 1 Bukan Tanaman - Wilda Aulia M.P; Lilik Purwastuty; Erwin Erwin (PAMPAS: Journal of Criminal Law, 2021)
This article aims to find out and analyze the basis for legal considerations of the Judge Decision Number 52 / Pid.Sus / 2019 / Pn. The research method used is a normative juridical. The results of the research show that the basis for the judge's consideration in imposing a sentence, the defendant was proven guilty. There are three basic considerations, namely consideration of juridical facts that the defendant is found guilty of committing a criminal act of not reporting the existence of a narcotics crime. The defendant was not the perpetrator who simply did not report a crime, but the perpetrator who kept methamphetamine and also acted as an intermediary for delivering methamphetamine as well. Whereas there were things that incriminated and lightened the defendant. The things that incriminated the defendant were that the defendant did not support the government program and what relieved the defendant, namely that the defendant was not convoluted in giving testimony, the defendant did not regret his actions, the defendant admitted frankly, and the defendant had never been convicted. Regarding the application of Article 131 of Law Number 35 of 2009 concerning Nakotika at the Sarolangun District Court, it has been applied in several cases that were tried at the Sarolangun District Court, and have been implemented properly, but there are several cases which according to the author the application of the article to the case is not right . Abstak Artikel ini bertujuan untuk untuk mengetahui dan menganalisis dasar pertimbangan hukum dari Hakim dalam menjatuhkan Pasal 131 dalam Putusan Nomor 52/Pid.Sus/2019/Pn.Srl. Metode penelitian yang digunakan adalah metode yuridis normatif. Ada tiga dasar pertimbangan yaitu Pertimbangan fakta yuridis bahwa terdakwa terbukti bersalah melakukan tindak pidana tidak melaporkan adanya tindak pidana narkotika. Pelaku bukan hanya tidak melaporkan adanya tindak pidana, melainkan pelaku yang menyimpan shabu dan juga sebagai perantara pengantaran shabu. Hal yang memberatkan terdakwa yaitu terdakwa tidak mendukung program pemerintah, terdakwa tidak menyesali perbuatannya. Hal yang meringankan terdakwa yaitu terdakwa tidak berbelit-belit dalam memberikan keterangan, terdakwa mengaku terus terang, dan terdakwa belum pernah dihukum. Mengenai penerapan Pasal 131 Undang-Undang Nomor 35 Tahun 2009 tentang Nakotika di Pengadilan Negeri Sarolangun, sudah diterapkan di beberapa kasus yang diadili di Pengadilan Negeri Sarolangun, dan telah diterapkan dengan baik, namun terdapat beberapa kasus yang menurut penulis penerapan pasal pada perkara tersebut kurang tepat.